(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aimed to determine the influence of administrative supervision manifested by the school heads on Private Higher Education Institutions’ (PHEIs) performance regarding programs accreditation in Region XII. The research employed ex-post facto research and the descriptive-correlation or the causal-comparative method since researchers investigated accessible documents on the accredited programs of PHEIs. The respondents of this study were the 410 school heads. The collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) software V.21X64. School heads of the Private Higher Education Institutions (PHEIs) demonstrated a marked display of their administrative supervision skills to support the school and improve the program accreditation. Also, higher education programs are primarily level 1 and level 2 accredited. Many of these programs are primary education, engineering, accountancy and business, nursing, and graduate degree programs. Few accredited programs were in level 3 and level 4. Most of these accredited programs are nursing, education, arts and sciences, accounting, financial management, and a graduate degree in education. These programs are offered chiefly by autonomous and deregulated PHEIs. A quarter of the 30 PHEIs have no accredited programs or membership in any accrediting agencies. Although PHEIs obtained lower accredited programs, monitoring and leading administrative supervision are good predictors of program accreditation. It is recommended that supervision must be sustained and strengthened among the regulated PHEIs to get their programs accredited and level up the accreditation of various programs.